The Correlation of Elevation, Soil Chemical Properties and Yield of Coffea arabica L. in Shaded Conditions: Yield of Coffea arabica L. in Shaded Conditions (Biological Sciences - PJSIR, 2022)
The research aims to analyze the correlation of altitude, soil chemical properties and shades on Arabica coffee yields in Humbang Hasundutan Regency Sumatera Utara Province. This research was conducted using survey method with purposive sampling approach. Sampling were conducted on altitude varied between 1200 - 1500 m asl. Soil samples in top soil and sub soil were taken in order to analyze pH, C, N, P205, K and cation exchange capacity (CEC). Coffee plant growth variables observed including productive branches, number of bunches, number of fruit per bunches, diameter of canopy and total yield, whereas the quality variable measured were physical quality and taste. Data on soil chemical properties, elevation, yield and coffee quality were analyzed using the correlation method. The results showed that under shaded condition, N, CEC, pH, K and P were positively correlated with height increase, while C- organic, productive branches, number of fruits per bunch and coffee production were negatively correlated. and whereas in the condition without shade, N, C, pH, K, productive branches, the number of fruit per bunch is negatively correlated with height increase, while CEC, P number of bunches, diameter of canopy and coffee yield are positively correlated. Statistical data shows that under shaded condition, the strongest correlation showed by pH and P average (0.999), whereas in an unshaded condition, yield and CEC showed the strongest correlation (0.994). In addition, shading affects on the taste of Arabica coffee at all elevation, namely the quality of flavour, body, quality after taste and balance.